Zum konventionell bedingten Kollokationsbegriff: das Konzept eines korpusbasierten bilingualen deutsch-polnischen Kollokationswörterbuches. On the term of convention-conditioned collocation: the conception of the corpus-based bilingual German-Polish Dictionary of Collocations. - Łyp-Bielecka, Aleksandra (Glottodidactica, 2016)
English is taught in almost all European countries as the first foreign language. German (similar to French) comes only to the rank of the second or even the third foreign language. This situation resulted in the introducing and in the rapid development of the tertiary language teaching and learning, whose main principles are inter alia: raising student’s awareness, reading comprehension as the basis of foreign language learning and the striving for the facilitating of the learning process. The article discusses whether and to what extent the above-mentioned principles are reflected in the selected GFL textbooks for beginners.